Hypnotherapy and Yoga Combination Decrease the Anxiety of Patients in Elective Preoperative - Basir Basir; Sidik Awaludin; Arif Imam Hidayat (Universitas Airlangga, 2020)
Introduction: Surgery is an experience that can cause anxiety, which, if not treated well, will cause some side effects. One of the forms of non-pharmacological therapy is hypnotherapy and yoga combination therapy. This study aimed to determine the effect of hypnotherapy and yoga combination therapy on anxiety scores in elective preoperative patients.Methods:This study used a quasi-experimental pretest and posttest with control group design. This study involved 17 respondents in the intervention group and 17 respondents in the control group. The sampling technique used consecutive sampling. Data collection used the instruments of The Amsterdam Preoperative Anxiety and Information Scale (APAIS). The statistical test used was the Mann-Whitney test.Results: The average age of respondents was 36.65 years old. In a majority, they were junior high school graduates who worked as employee. The major type of operation was tumor excision. The average anxiety scores before treatment in the intervention group were 14.71 (moderate anxiety) and decreased after being given hypnotherapy and yoga combination therapy to 9.47 (mild anxiety). The average anxiety scores before treatment in the control group were 15.71 (moderate anxiety) and decreased after deep breathing therapy to 13.76 (moderate anxiety). The difference test in anxiety scores of the intervention and control groups obtained p-value 0.015.Conclusion:Hypnotherapy and yoga combination therapy can reduce anxiety scores in elective preoperative patients.